2017
DOI: 10.1007/s40858-017-0182-0
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum species causing anthracnose on lima bean in Brazil

Abstract: The taxonomy of the genus Colletotrichum has undergone various changes. These alterations arise from the use of modern molecular tools. Currently, Colletotrichum species are grouped into complexes. Species of Colletotrichum associated with diseases in lima bean have been investigated very little. In Brazil, anthracnose in lima bean has often been associated with Colletotrichum truncatum, but only morphological characteristics have been used for identification purposes. In this study, samples of lima bean with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
14
1
5
Order By: Relevance
“…C. cliviae was originally described without mention to the perfect stage (Yang et al 2009), but occurrence of the sexual stage was later reported on Orchidaceae in China by Yang et al (2011) (asci 60-82 μm × 9.5-14 μm, ascospores 12.5-21.5 μm × 5-7.5 μm). In addition, just as this paper was being submitted to publication, Sousa et al (2017) have reported C. cliviae causing anthracnose on lima bean (Phaseolus lunatus L.), in the warm Brazilian states of Piauí and Alagoas, and also recorded formation of the sexual stage. Reported metrics for ascospores in that paper were 7.1-13.4 μm × 1.8-6.8 μm.…”
Section: Resultsmentioning
confidence: 92%
“…C. cliviae was originally described without mention to the perfect stage (Yang et al 2009), but occurrence of the sexual stage was later reported on Orchidaceae in China by Yang et al (2011) (asci 60-82 μm × 9.5-14 μm, ascospores 12.5-21.5 μm × 5-7.5 μm). In addition, just as this paper was being submitted to publication, Sousa et al (2017) have reported C. cliviae causing anthracnose on lima bean (Phaseolus lunatus L.), in the warm Brazilian states of Piauí and Alagoas, and also recorded formation of the sexual stage. Reported metrics for ascospores in that paper were 7.1-13.4 μm × 1.8-6.8 μm.…”
Section: Resultsmentioning
confidence: 92%
“…Colletotrichum cliviae Yan L. Yang et al. was reported as an anthracnose pathogen of Arundina graminifolia , Capsicum sp., Clivia miniata , Cymbidium hookerianum and Zamioculas zamiifolia in China ( Diao et al., 2017 , Yang et al., 2009 , Yang et al., 2011 , Zhou and Li, 2017 ) and of soybean, lima bean and grapevine in Brazil ( Santos et al., 2018 , Sousa et al., 2018 , Barbieri et al., 2017 ), on Cattleya sp. , Calamus thwaitesii , Phaseolus sp.…”
Section: Resultsmentioning
confidence: 99%
“…were revealed to be C. plurivorum as well. Strains from studies on lima beans ( Phaseolus lunatus ) in Brazil ( Sousa et al., 2018 , Cavalcante et al., 2018 ) probably also belong to this species, based on sequence comparisons of GAPDH and ACT sequences ( TUB2 was mixed-up with a C. truncatum strain) or a multilocus phylogeny, respectively. Many species have been reported or were described from these hosts ( Farr & Rossman 2017 , this study).…”
Section: Resultsmentioning
confidence: 99%
“…The C. fructicola species was originally reported to cause anthracnose on coffee fruit in Thailand (Prihastuti et al., ). This pathogen had been previously reported on Manihot sculenta, Nopalea cochenillifera , Annona muricata , Annona squamosal , Mangifera indica , Phaseolus lunatus and Malus domestica in Brazil (Bragança, Silva, Haddad, & Oliveira, ; Conforto, Lima, Garcete‐Gomez, Câmara, & Michereff, ; Costa et al., ; Lima et al., ; Sousa et al., ; Velho, Alaniz, Casanova, Mondino, & Stadnik, ).…”
Section: Discussionmentioning
confidence: 68%